2018
DOI: 10.1016/j.jecp.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Attentional control and executive functioning in school-aged children: Linking self-regulation and parenting strategies

Abstract: Good parenting strategies can shape children's neurocognitive development, yet little is known about the nature of this relation in school-aged children and whether this association shifts with age. We aimed to investigate the relation between parenting strategies observed during a home visit and children's performance-based attentional control and executive functioning (N=98, aged 4-8years). Linear and curvilinear regression analyses showed that children of parents who were more supportive, were less intrusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 63 publications
2
25
0
2
Order By: Relevance
“…Especially, children with ASD might need extra parental support and scaffolding to improve their emotion control and recognition. As a recent study showed in TD children, parents need to be able to adapt their levels of support depending on the child's needs (Spruijt, Dekker, Ziermans, & Swaab, 2018). Furthermore, emotional functioning requires not only early and sensitive interactions between caregivers and their children but also opportunities for incidental learning, that is, unintentional learning by overhearing and observing others.…”
Section: Internalizing Problemsmentioning
confidence: 99%
“…Especially, children with ASD might need extra parental support and scaffolding to improve their emotion control and recognition. As a recent study showed in TD children, parents need to be able to adapt their levels of support depending on the child's needs (Spruijt, Dekker, Ziermans, & Swaab, 2018). Furthermore, emotional functioning requires not only early and sensitive interactions between caregivers and their children but also opportunities for incidental learning, that is, unintentional learning by overhearing and observing others.…”
Section: Internalizing Problemsmentioning
confidence: 99%
“…This is an important period, given that executive functions are rapidly developing (Garon et al, 2008). However, some research has suggested that parenting must be adapted to accommodate the needs of the developing child, especially for IC (Spruijt, Dekker, Ziermans, & Swaab, 2018). Therefore, multiple aspects of parenting across early development should be considered in future studies.…”
Section: Future Directionsmentioning
confidence: 99%
“…The strong interindividual variability in attention performance depends on a number of factors, both constitutional and environmental, that determine the different developmental paths that attention could follow. Thus, as with all cognitive skills which are developed, in order to be understood and evaluated as fully as possible, consideration should be given to the child’s characteristics, taking into account the influence of many factors [16]: the biological characteristics of the child (i.e., temperamental characteristics favouring girls for effortful control and boys for surgency [17], maturation levels of the central nervous system (activation and visual spatial attention that show earlier development than other executive functions [8], general cognitive and emotional capacity of the child [2], and environmental variables, namely his/her personal experiences and the context in which he/she lives (for example, supporting parenting strategies) [18]. As far as environmental variables are concerned, we take into consideration the primary school experience because this period is characterized by rapid changes in attention functions according to the literature, and thus the role of attention in academic learning and achievement may be critical [19,20].…”
Section: Introductionmentioning
confidence: 99%